INVESTIGATING POINTS-OF-GENERATION POWER LOSSES ON THE NIGERIAN NATIONAL GRID FOLLOWING UNBUNDLING OF THE ELECTRIC UTILITY INDUSTRY - AJEWOLE TITUS OLUWASUJI; OLABODE OLAKUNLE ELIJAH; OKAKWU IGNATIUS KEMA; EGBEDINNI OLAKUNLE FEMI (Journal of Engineering Studies and Research)
Aside from the domino effects of being radial in structure, the Nigerian national electric grid is currently suffering from deteriorated infrastructures and unpredictable fuel supply for power generation. Massive introduction of green energy-based microgrid alternatives has been proposed as a major means of resolving the challenges. Such paradigm shift needs to be substantiated within the context of the present situation of the grid, for the consumption of policy makers and implementers, hence; the performance of the generation sub-system of the grid in the post-deregulation era is evaluated in this study. Two-year numerical data on the operational capacities of the twenty-nine power plants that are currently connected to the grid are employed to profile the behaviours of the plants over the period. Yearly averages of the three operational capacities of each plant are estimated, and by comparing the respective capacities, generation losses are computed for each of the plants. With 5,063.8 MW yearly average generation capacity in the year 2018, a loss of 61.02 % was experienced on the sub-system; while the generation loss was 61.55 % in the year 2019 that has yearly average generation capacity of 5,062.5 MW. For the two years combined, the average generation capacity is 5,063.2 MW at 61.36 % power loss. These estimations reveal that the pre-deregulation loss profile of the generation sub-system has not been curtailed despite the unbundling of the electric power industry. Generation loss has rather persisted and keeps taking a heavy toll on the electric utility market of the country. Significant deployment of renewable electricity microgrid is therefore required to provide enduring solution.